Factors Influencing the Discovery of Suspected Tuberculosis during the COVID-19 Pandemic in Palu City - Hasanah; Basir, Muafiah; Herawanto; Rau, Muh. Jusman (Journal of Health and Nutrition Research, 2022)
This study aimed to analyze the factors that influence the discovery of suspected tuberculosis during the COVID-19 pandemic in Palu City with a type of cross-sectional study. The type of research used was quantitative, with an analytic epidemiological study design using a cross-sectional design. This research was carried out in 13 working areas of the Puskesmas in Palu City from January to March 2022. The population in this study were all suspected tuberculosis at 13 Community Public Health (in Indonesia: Puskesmas) in Palu City in 2021, recorded at the Tuberculosis Information System totaling 15,620 people using the slovin formula to obtain a sample of 100 and the sampling design used stratified random sampling. This study used the T-test with α=10%. The results show that most of the respondents had less knowledge of 69 respondents (69%), respondents had a low stigma of 70 respondents (70%), 73 respondents (73%) received adequate tuberculosis services, 19 respondents (19%) received good services, and 8 respondents received less services, with a percentage of 8%. A significant effect between knowledge of suspected tuberculosis (p = 0.000), stigma (p = 0.000), and tuberculosis services (p = 0.000) on the discovery of suspected tuberculosis during the COVID-19 pandemic in Palu City. It is recommended to increase tuberculosis tracking during the COVID-19 pandemic conditions and conduct training to improve and optimize the role of tuberculosis cadres in the working area of each Public Health Center